EFFECTIVENESS OF SOURSOP LEAF EXTRACT To Microsporum gypseum CAUSE DERMATITIS COMPLEX ON DOG - Serlin, Angelina; Suartha, I Nyoman; Rompis, Aida Louise Tenden (Buletin Veteriner Udayana, 2020)
Soursop leaf ( Annona muricata L) contains active compounds such as flavonoids, saponins, and tannins that act as antifungals. This study aims to determine the ability of soursop leaf extract in inhibiting the growth of Microsporum gypseum, which causing dermatitis complex in dogs. The ability of soursop leaf extract to inhibit the growth of M. gypseum was tested using the agar plate diffusion method (Kirby Bauer) with slight modification. Complete randomized design (RAL) with four treatment, i.e., soursop leaf extract 0%, 5%, 10%, and 25%, with four replication and ketoconazole as a positive control was used in the study. The results showed that the inhibitory zones formed at concentrations of 5%, 10%, and 25% were 2.50 mm ± 0.00, 3.55 mm ± 0.00, and 5.00 mm ± 0, 58, respectively. Statistically, there was a highly significant difference ( p <0.01 ) between the average inhibitory zone of each treatment. Conclusion based on the test effectiveness of the soursop leaf extract is able to inhibit the growth of M. gypseum, which causing dermatitis complex in dogs.